ORAL HEALTH CONDITION OF STUDENTS ASSISTED BY THE STUDENT ASSISTANCE NATIONAL PROGRAM IN UFPA - Silva, Ana Carolina Santiago da; Medeiros, Amanda Menezes; Branco, Dimitra Castelo; Oliveira, Erick Ely Gomes de; Chermont, Armando Brito; Nascimento, Liliane Silva do (Journal of Health Care, 2018)
Introduction: The students health policy includes comprehensive care and aims to ensure better health for the university population. Public higher education institutions develop health care projects in order to promote students’ interaction and learning. Objective: The objective of this study was to evaluate the oral health status of students assisted by the Student Assistance National Program (PNAES). Materials and methods: The research was conducted at Universidade Federal do Pará and it analyzed the oral health of dental care projects’ users. The sample consisted of 250 undergraduate students of Belém campus. Data collection was made by means of oral clinical examination and questionnaire filling; this data underwent statistical analysis with BioEstat software 5.0 and R 3.3.1. Results: The students who are PNAES users are predominantly female, Brazilian, single, who have no children, live with their parents and have a family income of up to 3 minimum wages; the average DFMS found was 8.3; 74.4% of the individuals presented gingival bleeding, dental calculus and/or periodontal pocket, and 97.6% of them look for public hospitals when they get sick. Conclusion: Most students presented some dental or mouth discomfort and were dissatisfied about their oral health condition. The awareness of oral health status of these students allows the institution to know the profile of assistance projects users and to develop internal policies geared to assist their students in a vulnerable condition more effectively.